2017
DOI: 10.1111/1467-8500.12287
|View full text |Cite
|
Sign up to set email alerts
|

Attempting to Cultivate Mindsets for Boundary Spanning in Remote Indigenous Policy

Abstract: Collaboration is held to be an essential element of addressing complex problems. However, it is difficult to achieve, as it is often in tension with bureaucratic mindsets and traditions. Recently, Williams (2013) has suggested that all policy bureaucrats and program managers required to be involved with collaboration need to ‘span boundaries’ – to develop the capacity to build effective relationships, be able to engage ‘deeply’ with different parties, and understand and value multiple perspectives. A recent go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Given these very different understandings of the term, it is reasonable to expect that, without specific guidance, diverse public managers would seek to create public value through co‐production in very different ways. But it is also likely that the public managers putting forward ideas consistent with community development approaches might be expected to be more open to implementing co‐production than those suggesting the more managerialist notions of ‘wide engagement’ (Brown ). A common factor among those who adhered to the managerialist viewpoint was that their careers had been confined to the public sector.…”
Section: Empirical Findings (3)—building Public Valuementioning
confidence: 99%
“…Given these very different understandings of the term, it is reasonable to expect that, without specific guidance, diverse public managers would seek to create public value through co‐production in very different ways. But it is also likely that the public managers putting forward ideas consistent with community development approaches might be expected to be more open to implementing co‐production than those suggesting the more managerialist notions of ‘wide engagement’ (Brown ). A common factor among those who adhered to the managerialist viewpoint was that their careers had been confined to the public sector.…”
Section: Empirical Findings (3)—building Public Valuementioning
confidence: 99%
“…Outside more clearly defined organizations, 11 studies identified “community” as an entity into which or from which boundaries were spanned.. “Community” often seemed to refer to a local population; for example, “boundary spanners who broker connections between the school district and the community” (Brown, 2017, p. 369) or “reaching beyond clinic walls to create community linkages” (Etz et al, 2008, p. 391). At other times, studies more explicitly referred to communities defined by ethnic or cultural connections (Carlsson & Pijpers, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…It is apparent from the number of studies identified both that boundary-spanning is drawn upon as a concept to understand and frame what is happening in local settings and that it is applied to collaborations involving a host of different organizations and sectors. Notably, despite one paper’s reference to the “lack of definitional clarity” around boundary spanning (Brown, 2017), a relatively solid core definition surfaced in the research examined, centered on boundary spanning as facilitating some collaboration between systems that often have different languages and priorities. The divergences center mostly on the scope of what this involves.…”
Section: Discussion: Theorizing Boundary-spanning Beyond Formal Organ...mentioning
confidence: 99%
“…A multilateral approach has been supported by successive Ministers for Indigenous Affairs and Prime Ministers (Brown, 2017; Marsh et al., 2017). A decisive shift in this direction occurred through the 2007 National Partnership Agreement on Remote Service Delivery associated with the Close the Gap targets.…”
Section: Resultsmentioning
confidence: 99%